CTP synthase is essential for early endosperm development by regulating nuclei spacing - Yoon, Jinmi; Cho, Lae-Hyeon; Kim, Sung-Ryul; Tun, Win; Peng, Xin; Pasriga, Richa; Moon, Sunok; Hong, Woo-Jong; Ji, Hyeonso; Jung, Ki-Hong; Jeon, Jong-Seong; An, Gynheung (Wiley, 2021)
Cereal grain endosperms are an important source of human nutrition. Nuclear division in early endosperm development plays a major role in determining seed size; however, this development is not well understood. We identified the rice mutant endospermless 2 (enl2), which shows defects in the early stages of endosperm development. These phenotypes arise from mutations in OsCTPS1 that encodes a cytidine triphosphate synthase (CTPS). Both wild‐type and mutant endosperms were normal at 8 h after pollination (HAP). In contrast, at 24 HAP, enl2 endosperm had approximately 10–16 clumped nuclei while wild‐type nuclei had increased in number and migrated to the endosperm periphery. Staining of microtubules in endosperm at 24 HAP revealed that wild‐type nuclei were evenly distributed by microtubules while the enl2‐2 nuclei were tightly packed due to their reduction in microtubule association. In addition, OsCTPS1 interacts with tubulins; thus, these observations suggest that OsCTPS1 may be involved in microtubule formation. OsCTPS1 transiently formed macromolecular structures in the endosperm during early developmental stages, further supporting the idea that OsCTPS1 may function as a structural component during endosperm development. Finally, overexpression of OsCTPS1 increased seed weight by promoting endosperm nuclear division, suggesting that this trait could be used to increase grain yield.